A meta‐analysis of the relationship between VEGFR2 polymorphisms and atherosclerotic cardiovascular diseases. Issue 10 (24th July 2019) - Wang, Li; Ge, Hui; Peng, Longyun; Wang, Bing
Abstract: Background: Some previous studies explored associations between vascular endothelial growth factor receptor 2 ( VEGFR2 ) polymorphisms and atherosclerotic cardiovascular diseases (ASCVD), with conflicting findings. Hypothesis: We thought that VEGFR2 polymorphisms may influence susceptibility to ASCVD. Here, we aimed to better analyze the relationship between VEGFR2 polymorphisms and ASCVD in a larger combined population by performing a meta‐analysis. Methods: We searched Pubmed, Embase, and Web of Science for related articles. We calculated odds ratio (OR) and 95% confidence interval (CI) to estimate whether there are genetic associations between VEGFR2 polymorphisms and ASCVD. Results: Ten studies were included for this meta‐analysis (5474 cases and 8584 controls). VEGFR2 rs1870377 (dominant comparison: 0.81 (0.73‐0.89), I 2 = 56%; recessive comparison: 1.40 (1.25‐1.57), I 2 = 34%; allele comparison: 0.81 (0.76‐0.87), I 2 = 0%), rs2071559 (dominant comparison: 0.83 (0.76‐0.91), I 2 = 0%; recessive comparison: 1.22 (1.07‐1.38), I 2 = 0%; allele comparison: 0.86 (0.81‐0.92), I 2 = 0%) and rs2305948 (dominant comparison: 0.79 (0.72‐0.87), I 2 = 25%; recessive comparison: 1.44 (1.08‐1.92), I 2 = 60%; allele comparison: 0.79 (0.68‐0.92), I 2 = 73%) polymorphisms were all found to be significantly associated with susceptibility to ASCVD in general population. Subgroup analyses by type of disease revealed similar significant findings for rs1870377, rs2071559, and rs2305948 polymorphisms in coronary artery disease (CAD) subgroup. Besides, positive results were also found for rs1870377 polymorphism in ischemic stroke (IS) subgroup. Conclusions: In summary, this meta‐analysis proved that these VEGFR2 polymorphisms could be used to identify individual with elevated susceptibility to ASCVD.